Emerging Tuberculosis Pathogen Hijacks Social Communication Behavior in the Group-Living Banded Mongoose (Mungos mungo) - Alexander, Kathleen A. (mBio, 2016)
An emerging Mycobacterium tuberculosis complex (MTC) pathogen, M. mungi, infects wild banded mongooses (Mungos mungo) in Northern Botswana, causing significant mortality. This MTC pathogen did not appear to be transmitted through a primary aerosol or oral route. We utilized histopathology, spoligotyping, mycobacterial interspersed repetitive units-variable number of tandem repeats (MIRU-VNTR), quantitative PCR (qPCR), and molecular markers (regions of difference [RDs] from various MTC members, including region of difference 1 [RD1] from M. bovis BCG [RD1(BCG)], M. microti [RD1(mic)], and M. pinnipedii [RD1(seal)], genes Rv1510 [RD4], Rv1970 [RD7], Rv3877/8 [RD1], and Rv3120 [RD12], insertion element IS1561, the 16S RNA gene, and gene Rv0577 [cfp32]), including the newly characterized mongoose-specific deletion in RD1 (RD1(mon)), in order to demonstrate the presence of M. mungi DNA in infected mongooses and investigate pathogen invasion and exposure mechanisms. M. mungi DNA was identified in 29% of nasal planum samples (n = 52), 56% of nasal rinses and swabs (n = 9), 53% of oral swabs (n = 19), 22% of urine samples (n = 23), 33% of anal gland tissue (n = 18), and 39% of anal gland secretions (n = 44). The occurrence of extremely low cycle threshold values obtained with qPCR in anal gland and nasal planum samples indicates that high levels of M. mungi can be found in these tissue types. Histological data were consistent with these results, suggesting that pathogen invasion occurs through breaks in the nasal planum and/or skin of the mongoose host, which are in frequent contact with anal gland secretions and urine during olfactory communication behavior. Lesions in the lung, when present, occurred only with disseminated disease. No environmental sources of M. mungi DNA could be found. We report primary environmental transmission of an MTC pathogen that occurs in association with social communication behavior.